Penatalaksaan Kangaroo Mother Care (KMC) pada Bayi Prematur di Ruang NICU - Andi Nurhalimah Zakhra; Nur Ilah Padhila; Sunarti; Yusrah Taqiyah (Window of Nursing Journal, 2025)
The birth of premature babies remains one of the polemics and is a contributor to the highest mortality rates in the world. Kangaroo mother care is a solution that can maintain the baby's body temperature economically because it only uses a long cloth and the heat comes from the mother or father's body through skin-to-skin contact. The purpose of this study is to understand the implementation of kangaroo mother care in the NICU room at RSUD Labuang Baji, Makassar City. The research design used in this study is quantitative with a descriptive approach. The sample was determined using a total sampling method with a total of 18 respondents. The research instruments were questionnaires and observation sheets. The results of the study showed that all 18 respondents had carried out KMC according to SOP. Regarding the duration of KMC implementation, 7 respondents carried out KMC for <2 hours and 11 mothers carried out KMC for >2 hours. A total of 18 respondents performed intermittent KMC. A total of 18 respondents were fully supported by healthcare workers, partners, and family in carrying out KMC. The conclusion of this study is that the KMC management intervention has been implemented in accordance with SOPs. The duration carried out by respondents performing KMC varied and was done intermittently. Respondent support in the implementation of KMC has been good. All respondents received support from healthcare workers, husbands, and family.